The Effect of Behavioral Therapy with Modeling Techniques on Changes in the Adherence of Diabetes Mellitus Patients - Caturia Sasti Sulistyana; Rina Budi Kristiani (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2021)
Diabetes Mellitus (DM) is a disease whose prevalence is not infectious increases with changes in lifestyle. If not managed properly, it will cause various complications that reduce quality of life, increase morbidity and mortality, and harm the economy. The success of DM management is strongly influenced by the patient's adherence to medication and diet. One of the interventions to improve the adherence of DM sufferers is Behavior Therapy with modeling techniques. The purpose of this study was to analyze the effect of behavioral therapy with modeling techniques on changes in adherence of DM patients. The design of this study was quasy-experimental with pretest posttest and control group, on a sample of 40 DM patients with consecutive sampling technique. The intervention was carried out in 4 sessions for 2 weeks. The results of the statistical test paired sample t-test and independent sample t-test obtained p <0.5 (0.000), which meant that there was an effect of behavioral therapy with modeling techniques on changes in adherence DM patient. Changes in compliance that occurred between before and after the intervention was 16.95 points. Modeling technique is behavioral learning through observation of a model who has successfully controlled his illness to emphasize changes in mindset, beliefs, and commitment to a person's new positive behavior. Modeling has an impact not only on imitating, but also adding or subtracting the observed behavior, so that it can be applied to obtain new behavior, leave old negative behavior, and maintain the desired behavior.